Enhancing Subgrade Stability In Black Cotton Soil Using Coir Fiber And MicroShredded Waste Plastic: An Eco-Friendly Approach - Abararahemad A. Khalak; Dr. Jayesh Juremalani (Journal for ReAttach Therapy and Developmental Diversities, 2022)
This research paper investigates the stabilization of black cotton soil for road subgrade construction by integrating coir fiber and micro-shredded waste plastic powder (MSWPP), with a focus on environmental sustainability and economic efficiency. Traditional soil stabilization techniques, while effective, pose significant environmental and economic challenges. In response, this study evaluates the feasibility, optimal mix proportions, and enhancement of mechanical properties using sustainable materials. The chosen mix proportions for this investigation were specifically 0.3% coir fiber and 10% MSWPP by weight of dry soil. Extensive laboratory tests, including liquid limit, plastic limit, unconfined compressive strength (UCS), California bearing ratio (CBR), Proctor, free swell index, mechanical analysis, moisture content, specific gravity, direct shear, consolidation, tri-axial, and swelling pressure assessments, were conducted to assess the performance of soil samples stabilized with the specified proportions of coir fiber, MSWPP, and their synergistic combination. The research aims to provide a thorough analysis of how these materials, both separately and together, contribute to the soil stabilization process, with a particular focus on their impact on mechanical properties and costeffectiveness in comparison to traditional methods. The outcomes of this study aim to offer practical guidelines for the application of coir fiber and MSWPP in enhancing the durability and sustainability of road infrastructure constructed on black cotton soil, thereby filling a critical gap in sustainable civil engineering practices